Female Hormone Receptors are Differentially Expressed in Mouse Fibrocartilages - Wang, Wei (2008)
OBJECTIVE: Despite the female predilection for joint diseases, and the known effects of female hormones in regulating chondrocyte function, the various female hormone receptor subtypes in joints are not well characterized, and comparisons in receptor profiles between joints and genders is lacking. This investigation characterized and compared the relative levels of estrogen receptors (ER) –α and -β, relaxin receptors LGR7 and LGR8, and progesterone receptor (PR) in the temporomandibular joint (TMJ) disc, knee meniscus and pubic symphysis fibrocartilages. METHODS: Fibrocartilaginous cells from 12-week old mice were maintained in serum-containing α-MEM until confluence. Total RNA and cell lysates were assayed by RT-PCR, qRT-PCR, immunocytochemistry and Western blots, and joint sections subjected to immunohistochemistry. RESULTS: All hormone receptors assayed were present in the three joints, but showed substantial differences in expression levels between joints. TMJ cells had higher ER-α (>2.8-fold), ER-β (>2.2-fold), LGR7 (>3-fold) and PR (>1.8-fold), and lower LGR8 (0.5-fold) gene expression levels than knee meniscus cells. The ratio of ER-α:ER-β and LGR7:LGR8 was 1.8- and 7.5-fold higher, respectively, in TMJ than in knee meniscus cells. The profile of hormone receptors in the TMJ disc were similar to those in the pubic symphysis. Immunochemistry confirmed the differential expression patterns of these receptors in the three tissues. The TMJ cells demonstrated sexual dimorphism in the levels of PR. CONCLUSIONS: The findings suggest that these fibrocartilages are putative target tissues for actions of female hormones. The differential expression profiles of the hormone receptors in the three joint fibrocartilages and the sexual dimorphism in ERs in TMJ disc cells are likely to result in varied downstream effects in response to hormones within these fibrocartilaginous tissues.